Are the Indian corporates creating value through acquisitions in the US and European markets?. (2017) - Duppati, Geeta; Rao, Narendar V.; Locke, Stuart
This paper examines the stock market reactions to a sample of merger and acquisition (M&A) cases following the liberalisation of the policy regime by the Indian Government between 2000 and 2011. The stock market reacted differently to the announcements of overseas foreign direct investment related to M&As by Indian corporates. In some cases, the stock market reacted negatively in the short-term to the announcement but favourably in the post-acquisition period. In other cases, there was a favourable reaction or an unfavourable reaction in the short-term after the announcement and the longer term of the post-acquisition period. Drawing on secondary information, this paper offers explanations for the stock market reactions. Context is important and the specific characteristics of the Indian companies may have affected the outcomes. Though each case is unique, there are trends in approaches that are discernible. This paper also investigates the relationship between media coverage of company events such as announcements of mergers and acquisitions and the market reaction to such announcements. The results indicate that a variety of factors are responsible for overseas investment.